Description of the targeted water supply and hygiene response strategy implemented during the cholera outbreak of 2017–2018 in Kinshasa, DRC - Didier Bompangue (BMC Infectious Diseases, 2020)
Abstract Background Rapid control of cholera outbreaks is a significant challenge in overpopulated urban areas. During late-2017, Kinshasa, the capital of the Democratic Republic of the Congo, experienced a cholera outbreak that showed potential to spread throughout the city. A novel targeted water and hygiene response strategy was implemented to quickly stem the outbreak. Methods We describe the first implementation of the cluster grid response strategy carried out in the community during the cholera outbreak in Kinshasa, in which response activities targeted cholera case clusters using a grid approach. Interventions focused on emergency water supply, household water treatment and safe storage, home disinfection and hygiene promotion. We also performed a preliminary community trial study to assess the temporal pattern of the outbreak before and after response interventions were implemented. Cholera surveillance databases from the Ministry of Health were analyzed to assess the spatiotemporal dynamics of the outbreak using epidemic curves and maps. Results From January 2017 to November 2018, a total of 1712 suspected cholera cases were reported in Kinshasa. During this period, the most affected health zones included Binza Météo, Limeté, Kokolo, Kintambo and Kingabwa. Following implementation of the response strategy, the weekly cholera case numbers in Binza Météo, Kintambo and Limeté decreased by an average of 57% after 2 weeks and 86% after 4 weeks. The total weekly case numbers throughout Kinshasa Province dropped by 71% 4 weeks after the peak of the outbreak. Conclusion During the 2017–2018 period, Kinshasa experienced a sharp increase in cholera case numbers. To contain the outbreak, water supply and hygiene response interventions targeted case households, nearby neighbors and public areas in case clusters using a grid approach. Following implementation of the response, the outbreak in Kinshasa was quickly brought under control. A similar approach may be adapted to quickly interrupt cholera transmission in other urban settings.